A school-based oral health educational program: the experience of Maringa- PR, Brazil Programa educacional em saúde bucal baseado em escolas: a experiência de Maringá- PR, Brasil - Carlos Alberto Conrado; Sandra Mara Maciel; Márcia Regina Oliveira (University of São Paulo, 2004)
The main purpose of this study was to evaluate the preliminary results of a school-based oral health educational strategy adopted in public primary schools from the city of Maringa, State of Parana, Brazil. The study sample was composed by 556 children and adolescents aged 6 to 17 years old, 124 schoolteachers and a group of 55 mothers. The educational approach was implemented for 18 months and consisted of reinforcements of interventions addressed to students and schoolteachers at school level and few activities targeted at the mothers, performed by means of home visits. Baseline and follow-up interviews focused on oral health care were undertaken for the entire study population. As a stimulus for the students to achieve proper oral hygiene habits, the simplified oral hygiene index was assessed at three different moments. A statistically significant improvement in their oral hygiene index (p<0.001) was recorded. The results achieved suggest an encouraging tendency towards the improvement in the levels of oral health care among the school-age youths studied. They also point out the need of intensifying the preparation of schoolteachers in oral health topics, as well the instructions to the mothers for their oral health care. Moreover, they highlight the importance of the continuous implementation of school-based programs to promote the oral health. O principal propósito deste estudo foi avaliar os resultados preliminares de uma estratégia educacional baseada em escolas sobre saúde bucal adotada em escolas públicas de ensino fundamental da cidade de Maringá, estado do Paraná, Brasil. A amostra de estudo foi composta por 556 crianças e adolescentes entre 6 e 17 anos de idade, 124 professoras e um grupo de 55 mães. A abordagem educacional foi implementada por um período de 18 meses e consistiu de reforços das intervenções educativas dirigidas aos estudantes e professores a nível escolar e de poucas atividades tendo como alvo as mães, desenvolvidas através de visitas domiciliares. Entrevistas iniciais e de acompanhamento focando cuidados em saúde bucal foram realizadas com toda a população de estudo. Como um estímulo aos estudantes para assumirem hábitos apropriados de higiene bucal, o índice de higiene oral simplificado foi avaliado em três diferentes momentos. Uma melhora estatisticamente significante em seus índices de higiene oral (p< 0,001) foi registrada. Os resultados alcançados sugerem uma encorajadora tendência de melhoria nos níveis de cuidados em saúde bucal entre os jovens em idade escolar estudados. Eles, também, apontam para a necessidade de se intensificar o preparo das professoras em tópicos relacionados à saúde bucal, bem como a instrução das mães para os cuidados apropriados com a saúde bucal. Além disso, eles evidenciam a importância da contínua implementação de programas baseados em escolas para a promoção da saúde bucal.